Lithuanian monetary silver ingots in Kernavė - Bagdzevičienė, Jurga; Vėlius, Gintautas (Archaeologia Lituana, 2010)
A fragment of the Lithuanian monetary elongated bar-shaped ingot was first found in Lithuania in 1983 during archaeological excavations at the Obeliai Lake (Ukmergė District), in the layer of cremation burials (Urbanavičius, 1988, p. 40, pav. 64:7). During the last decades Lithuanian monetary silver ingots as well as their counterfeits are increasingly more often found during excavations. Six fragments of ingots in the shape of a semicircular rod, including one fake, were found during excavations at Vilnius Lower Castle. One of these finds has been published (Remecas, 2006, p. 8, 46). The site of the Lower Castle of Sovereigns has also yielded a trilateral ingot, recovered in a hoard along with 63 early coins of the Grand Duchy of Lithuania (Remecas, 2005, p. 315). Three fragments of a semicircular, rod-shaped ingot, including one fake, made of tin and copper alloy with lead additives, were recovered in an old grave in the territory of Verkiai homestead (Vilnius City). These money ingots were found in the rich male burial 12, deposited in a leather pouch together with a fire-steel and a razor (Žukovskis, 2009, p. 176). From 1985 to 2008 Kernavė yielded 19 fragments of money ingots in the shape of a semicircular rod and a hoard, comprising four ingots of this type (see table 1). A further Lithuanian elongated bar and half an ingot of a triangular cross-section of undefined provenance are stored in the collections of Kernavė Museum. In 1985 a hoard including four Lithuanian elongated bar ingots was found on the hillfort of the Castle Hill. The hoard is dated to the end of summer 1365, the time when the Teutonic troops burnt down Kernavė and Maišiagala on their march to Vilnius (Luchtanas, 2000, p. 71). In 1991 a fragment of the Lithuanian elongated bar ingot was recovered at a pine forest close to the Neris River, beside two fireplaces dating to the 13th–14th centuries (Luchtanas, 1992, p. 28). During excavations at the Aukuras (Offering) Hill in 1993 four fragments of money ingots were recovered in the cultural layer of the 13th–14th centuries. One of these was found to be a fake of silver-plated copper alloy (Luchtanas, 1994, p. 52). During excavations at the 13th–14th century Kernavė-Kriveikiškės burial ground in 1994 a fragment of a Lithuanian elongated bar was found in the arable soil. This monetary ingot most likely comes from a disturbed burial. The largest number of elongated Lithuanian bars – a total of eight fragments – was recovered in 1998–2001, during excavations at a 14th century homestead in the upper town of Kernavė, 140 m east of the hillfort of Mindaugas’ Throne (Vaičiūnienė, 2000, p. 133; 2002, p. 41; 2002, p. 59). The investigated place of the homestead is situated in a ravine, into which finds and the cultural layer from the nearby upper locations drifted in the course of time. It therefore remains unclear whether the ingot fragments had been hidden or lost. In 2002 a fragment of what then was taken for a further monetary ingot was found in a field northeast of the Lizdeika Hill hillfort. In 2004 and 2008 investigations were carried out at the site of a homestead in the upper Kernavė town, located about 120 m north of the Castle Hill hillfort and 4 more fragments of Lithuanian ingots were recovered in the 14th century cultural layer (Vaičiūnienė, 2006, p. 52; Baltramiejūnaitė, 2009, p. 331–332). Analysis of the chemical structure of metal alloys found at Kernavė revealed that not all of them qualify as fragments of Lithuanian bar ingots. Alloy N-615, found in 1991 in a pine forest near the Neris River is a doubtless forgery of the Lithuanian elongated bar, made of copper alloy and replicating the shape of an authentic Lithuanian ingot, cracked along prior notches. The results of the chemical analysis of the small ingot N-604 found in the upper town of Kernavė showed that it was a tin alloy. Nevertheless, the shape of the find suggests that it is a forgery of a monetary ingot. As a matter of fact, the basic material of counterfeits recovered at Verkiai (Vilnius) and the Lower Vilnius Castle was also tin. The shape and measurements of one ingot found on the hillfort of Aukuras Hill (N-559/1) bear close resemblance to a fragment of the Lithuanian bar ingot, while chemical analysis revealed it to be a lead alloy, possibly used as melting metal. Ingot N-614 found close to Lizdeika hillfort in 2002, which turned out to be bronze, can most probably be treated as raw metal resource. As the analysis of metal alloys enabled to establish authentic Lithuanian bar ingots and their counterfeits, an effort was made to trace the weight system of cracked or hacked fragments and find out whether such a system existed at all. It is obvious, however, that no frequent recurrence of similar weights can be seen. It is most likely that a certain part of an ingot was simply snapped or hacked off depending on the weight needed at a particular transaction. The archaeological evidence from investigations at Kernavė demonstrate that Lithuanian bar ingots or their fragments were frequently used as means of payment among townsfolk and quite many of them had been misplaced. It is noteworthy that the smallest 7 fragments, with their weight ranging from 0.54 g to 1.53 g, are almost as heavy as the first types of Lithuanian coins and could therefore be certainly used for small-scale transactions. A further important feature is the obvious falsification of the Lithuanian bar ingots used by townsfolk as well as frequent silver alloys of low standard. It is very likely that at the end of the pre-coinage period production of money ingots became uncontrollable on the state level. A morphological analysis of fragments of Lithuanian bar ingots revealed that the majority of ingot pieces had been cracked along prior notches. In case of need, a smaller fragment was hacked off. Hence, the functional intention of notches on the Lithuanian bar ingots is the possibility to split the ingot into smaller fragments.